1996
DOI: 10.1046/j.1365-3083.1996.d01-5.x
|View full text |Cite
|
Sign up to set email alerts
|

IFN‐γ Restores HIV‐ and Non‐HIV‐Specific Cell Mediated Immune Response In Vitro and Its Activity is Neutralized by Antibodies from Patients with AIDS

Abstract: The addition of IFN-gamma to cultures of peripheral blood mononuclear cells (PBMCs) obtained from asymptomatic HIV-infected patients increased cell proliferation in response to HIV envelope synthetic peptides (Env), influenza A virus (VIRUS), and allogeneic lymphocytes (ALLO) but not to phytohaemagglutinin (PHA) stimulation. F(Ab)2 fragments of IgG purified from the sera of HIV-seropositive patients specifically interfered with IFN-gamma-induced cell proliferation in response to recall antigens. Neutralization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…It is likely that the nature of mitogenic or antigenic stimulus influences not only the activation status of T cells but also their ability to undergo proliferation. Indeed PMA, which stimulates almost 100% of T cells to express CD69, does not significantly induce DNA synthesis in the absence of a calcium ionophore (5,11,15). Also, by detecting activation antigens expressed on T cells during the late-stage differentiation leading to proliferation as CD25, CD71, and HLA-DR, the percentage of positive lymphocytes and the amount of [ 3 H]thymidine incorporation were not found to correlate under any condition tested.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is likely that the nature of mitogenic or antigenic stimulus influences not only the activation status of T cells but also their ability to undergo proliferation. Indeed PMA, which stimulates almost 100% of T cells to express CD69, does not significantly induce DNA synthesis in the absence of a calcium ionophore (5,11,15). Also, by detecting activation antigens expressed on T cells during the late-stage differentiation leading to proliferation as CD25, CD71, and HLA-DR, the percentage of positive lymphocytes and the amount of [ 3 H]thymidine incorporation were not found to correlate under any condition tested.…”
Section: Discussionmentioning
confidence: 88%
“…Successful immune response to an infectious agent depends on the activation and proliferation of appropriate immune-competent cells. The standard way to quantify in vitro cellular immune response to a microorganism is the measurement of cell proliferation as a function of tritiated [ 3 H]thymidine incorporation, after contact between cultured lymphocytes and the microorganism or its specific antigen(s) (4,5). This assay has the disadvantage of being performed on bulk cultures and, unless lymphocyte subsets are purified, it provides no information on the cell subpopulations involved in antigen recognition or bearing functional defects.…”
mentioning
confidence: 99%
“…Impaired proliferative response of T-lymphocytes to antigenstimulation is related to the stage of disease [193][194][195], stimulated PBMC of HIV infected patients produce lower amounts of IL-2 as well as IFN-as PBMC of healthy controls [190]. Interestingly, exogenous substitution of cytokines is able to restore the proliferative response to antigens markedly in vitro [196,197], whereas systemic administration of IFN-may rather result in an impaired proliferative response to mitogens [43]. A study performed in 1988 first showed that increased serum neopterin concentrations in HIV infected patients were associated with diminished IFN--production of lymphocytes upon stimulation in vitro [191].…”
Section: Ido and Other Ifn--mediated Pathways In The Development Of Imentioning
confidence: 99%
“…HIV may evade CTL through a number of mechanisms including generation of escape mutants, deletion or dysregulation of CD4 ϩ Th cells, and dendritic cell dysfunction (10,11). Some acquired CTL dysfunction may be mediated by defects in expression of perforin or granzyme B (12), chemokine defects (13) or Abs (14).…”
Section: Hiv Antigens Can Induce Tgf-␤ 1 -Producing Immunoregulatory mentioning
confidence: 99%